Water soluble compounds in size-segregated Arctic aerosol at Gruvebadet, Ny-Ålesund in 2013, 2014, 2015 and 2018-2019 - Matteo Feltracco; Elena Barbaro; Andrea Spolaor; Marco Vecchiato; Alice Callegaro; Francois Burgay; Massimiliano Vardè; Niccolò Maffezzoli; Federico Dallo; Federico Scoto; Clara Turetta; Roberta Zangrando; et al. (2021)
Water Soluble Organic Compounds (WSOCs) chemistry in the Arctic region occurs through several sources, depending on the considered compound. We examine here L- & D- Free and Combined amino acids, mono-saccharides, di-saccharides, anhydro-sugars, alcohol-sugars, organic acids and major cations and anions in 2013, 2014, 2015 and 2018 Arctic campaign at Gruvebadet Laboratory, close to Ny-Ålesund (Svalbard Island - 78°55′03′′N, 11°53′39′′E). A multi-stage Andersen impactor (TE-6000 series, Tisch Environmental Inc.) was used to collect aerosol samples on six pre-combusted (4 h at 400 °C in a muffle furnace) quartz fiber filters. The sampler accumulated particles with a cut-off diameters of 10.0 μm, 7.2 μm, 3.0 μm, 1.5 μm, and 0.95 μm on slotted filters and <0.49 μm on backup filter. The frequency of sampling varied from 1 to 10 days with a total air volume of about 1000 or 15000 m3 per sample.